Does negative information about aging influence older adults' physical performance and subjective age?. (September 2018) - Marquet, Manon; Boutaayamou, Mohamed; Schwartz, Cédric; Locquet, Médéa; Bruyère, Olivier; Croisier, Jean-Louis; Adam, Stéphane
Highlights: Stereotype threat effects on older adults' physical performance are not significant. Older people feel mentally and physically older in a stereotype threat situation. Threat effects on physical subjective age are moderated by self-perceptions of aging. Abstract: This study investigated the way negative stereotypes influence older adults' physical performance and how old they feel mentally and physically. Sixty-four older adults aged 65 years and older performed different physical tasks using a 3D optoelectronic system under a low or high stereotype threat condition. Self-perceptions of aging were considered as a moderator of the effects of threat. Overall, the effects of threat on physical performance were mostly not significant across tasks. However, threat condition influenced older adults' mental subjective age after they had performed the physical tests; people in the high-threat condition felt closer to their chronological age. Threat also influenced participants' physical subjective age, and this effect was moderated by self-perceptions of aging. More precisely, participants in the high-threat condition felt 7% physically older than their chronological age when they had more negative self-perceptions, while participants in the low-threat condition felt 13% younger. No differences emerged for participants who had more positive self-perceptions. The present findings suggest that performing physical tests under stereotype threat might worsen older people's subjective experience of their own aging by making them feel older.